An Evaluation of English Coursebooks for Young Learners - Diptoadi, Veronica Listiani; Mindari, Ruruh (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This study evaluates two English coursebooks used at Wima Kids English Course, Hip Hip Hooray and Backpack, to determine whether they fulfill the objectives of teaching English at Wima Kids and whether they are designed in accordance with the principles of Teaching English to Young Learners (TEYL). It also examines the aspects in which Hip Hip Hooray can be complemented by the materials in Backpack. The instruments used in this study were the researchers themselves, equipped with Bilash’s (2009) Evaluation Checklist, and in-depth interviews with teachers who had used both coursebook series in their classes. Using the checklist, it was found that Hip Hip Hooray and Backpack are consistent with the objective of teaching English at Wima Kids, namely helping learners use English for communication, especially oral communication. Both series also fulfill the principles of TEYL. Furthermore, the findings reveal that Backpack can complement the Hip Hip Hooray series in terms of language content, topic content, teaching tips and techniques, and grammar activities.